(untitled) (AYUSHDHARA, 2023)
Kitibha of Ayurvedic literature is compared and accepted with Psoriasis. It pacifies Vata and Kapha Dosha. Scalp Psoriasis is a widespread condition of the skin, which causes elevated, reddish, sometimes skinny spots. It may occur as one or several patches and even affect the whole scalp. Objective: To see the effect of Ayurvedic drugs and local applications can help in Kitibha kushtha. Methodology: In this case, a 20-year male patient had been experiencing symptoms of Reddish-white patches over-head, scaling of skin, Itching all over body. Ayurvedic medicines were used in the study for two months. Discussion: The major goal of the treatment is to help to eliminate scales. The medicines were used in the study also purify the impure blood. Ashtmurti Rasayana, Gandhaka Rasayan both are blood purifier also work as broad-spectrum antibiotics Ashtmurti Rasayana has Jantughna property. Panch Nimba Churna is purifying in nature. Rasa Manikya has antimicrobial property and balances Vata- Kapha dosha. It removes Ama (toxins) accumulated under the skin. Godanti helps in Pitta balance and anti-inflammatory property. Conclusion: Each science has its own fundamentals of the management and success rate with its own limitations. But still now an effective and promising cure for Psoriasis is not found. So, there is need of era to develop some Ayurveda treatment modalities for Psoriasis. Keeping the fundamentals of management in mind the current study was conducted which will be helpful for curing the Kitibha Kushtha (Psoriasis).